Evaluation and Assessment Innovation Challenges and Opportunities in PAI Learning: Building a Competitive Generation (Students) in the 21st Century - Al-Banjari, Faisal; Wahab, Wahab (Al-Ulum: Jurnal Pendidikan Islam, 2025)
This study aims to discuss innovations in evaluation and assessment in Islamic Religious Education (PAI) learning in order to face challenges and take advantage of opportunities to build a competitive generation in the 21st century. The method in this study is a qualitative method of literature study taken from several journals, articles or internet ebooks. The result of this discussion is that in the era of globalization full of technological advances and social changes, the traditional evaluation system in PAI learning is considered less able to accommodate the development of 21st century competencies, such as critical thinking, creativity, collaboration, and digital literacy. Through evaluation innovations, such as the use of digital technology and assessment methods that focus on continuous learning, this article examines how educators can prepare students with relevant skills to compete in a global world. Innovation in evaluation in PAI is needed to improve student competence in the digital era. The use of technology and continuous learning methods can be a solution to global challenges, with opportunities for optimization through collaboration and technology utilization.